(untitled) (Research, Society and Development, 2025)
Insulin resistance (IR), defined as decreased cell sensitivity to the action of insulin, is a relevant risk factor for the development of chronic non-communicable diseases (NCDs). In recent decades, the sharp increase in obesity rates and sedentary lifestyles among adolescents has contributed significantly to the increased prevalence of this metabolic dysfunction. This study aims to investigate the relationship between IR and behavioral, dietary, genetic, and psychosocial factors that affect the adolescent population. Evidence indicates that inadequate dietary patterns, characterized by excessive consumption of sugars and ultra-processed foods, associated with physical inactivity, play a determining role in the emergence of IR. Furthermore, socioeconomic, cultural, and family environment factors have been shown to have a direct influence on the dietary choices and lifestyle of young people, increasing metabolic risk. To achieve the proposed objectives, a literature review will be carried out based on scientific articles available in the PubMed and SciELO databases, among others, with the inclusion criteria being articles published in the last ten years and clinical trials related to the topic.